2010
DOI: 10.1128/jvi.00650-10
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Severe Acute Respiratory Syndrome-Related Coronavirus in European Bats and Classification of Coronaviruses Based on Partial RNA-Dependent RNA Polymerase Gene Sequences

Abstract: Bats may host emerging viruses, including coronaviruses (CoV). We conducted an evaluation of CoV in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
397
3
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(443 citation statements)
references
References 60 publications
22
397
3
8
Order By: Relevance
“…Equally, although the first cases were all connected with the MiddleEast, it is noticeable that they came from widely separated places. Since similar animal coronaviruses can be found in bats in all regions of the world, it is possible that these infections are to be found sporadically in many countries [7][8][9][10][11][12]. This makes a strong case for further studies of animal coronaviruses and prospective and retrospective searches for cases in other regions.…”
Section: Background Informationmentioning
confidence: 99%
“…Equally, although the first cases were all connected with the MiddleEast, it is noticeable that they came from widely separated places. Since similar animal coronaviruses can be found in bats in all regions of the world, it is possible that these infections are to be found sporadically in many countries [7][8][9][10][11][12]. This makes a strong case for further studies of animal coronaviruses and prospective and retrospective searches for cases in other regions.…”
Section: Background Informationmentioning
confidence: 99%
“…Between 2003 and, the severe acute respiratory syndrome (SARS)-CoV caused a worldwide epidemic and had a significant economic impact in the countries where the disease outbreak occurred [8]. Phylogenetic analyses have shown that SARS-CoV is closely related to the sequences of the betacoronaviruses [9]. In 2004, another alphacoronavirus (HCoV-NL63) was isolated from a 7-month-old child in the Netherlands suffering from bronchiolitis and conjunctivitis [7].…”
Section: Introductionmentioning
confidence: 99%
“…N and C-terminal tail peptide bind by cosedimentation in solution (View interaction) N and N bind by cosedimentation in solution (View Interaction: 1,2,3,4,5,6,7,8,9,10,11,12) C-terminal tail peptide and N bind by fluorescence technology (View interaction) N and N bind by cross-linking study (View interaction) N and N bind by cross-linking study (View Interaction: 1,2,3,4) Crown…”
Section: Structured Summary Of Protein Interactionsmentioning
confidence: 99%
“…The majority of these CoVs originated from African, Asian and European bats (Chu et al, 2006;Drexler et al, 2010Drexler et al, , 2011Gloza-Rausch et al, 2008;Pfefferle et al, 2009;Poon et al, 2005;Quan et al, 2010;Tang et al, 2006;Tong et al, 2009). In addition to SARS-CoV, four human coronaviruses (HCoVs), termed HCoV-OC43, -229E, -NL63 and -HKU1 are known (Drosten et al, 2003;Fouchier et al, 2004;Gaunt et al, 2010;Hamre & Procknow, 1966;McIntosh et al, 1967;van der Hoek et al, 2004;Weiss & Navas-Martin, 2005;.…”
Section: Introductionmentioning
confidence: 99%